2011
DOI: 10.1136/emj.2010.104687
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of intravenous paracetamol and intravenous morphine for acute traumatic limb pain in the emergency department

Abstract: Intravenous paracetamol appears to provide a level of analgesia comparable to intravenous morphine in isolated limb trauma. Further larger studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 9 publications
1
77
0
2
Order By: Relevance
“…Results of the similar studies did not show any significant difference in the analgesic effect of intravenous acetaminophen and morphine (3)(4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Results of the similar studies did not show any significant difference in the analgesic effect of intravenous acetaminophen and morphine (3)(4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 81%
“…A single-blind emergency department study over patients presenting with renal colic found that intravenous acetaminophen was equally effective as intravenous morphine (3). There are also some other studies showing that intravenous acetaminophen is as effective as intravenous morphine in pain management (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…19 Intravenous paracetamol 1 gram has analgesic activity in moderate to severe post-operative pain similar have shown ketorolac 30 milligram 20 diclofenac 75 miligram, 21 morphine 10 miligram. 22 It also demonstrated that Intravenous paracetamol reduce the use of opioid. It reduces the need for the patient's total opioid by 24-46% and increase in patient satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…Intravenous acetaminophen is being studied for acute pain such as in acute traumatic limb injuries [45] or rib fractures [46] or in postoperative patients [47,48]. It has also been shown to reduce the need for rescue pain medications such as opioids [49,50].…”
Section: Acetaminophenmentioning
confidence: 99%